University students’ perception to online class delivery methods during the COVID-19 pandemic - Jeong-Ja Choi; Charles Arthur Robb; Mazalan Mifli; Zaliha Zainuddin (Elsevier Ltd, 2021)
The general process of learning in educational institutions around the globe has changed since the advent of the COVID-19 virus. Educational sectors in all nations are forced to adapt and rearrange their compositions and systems as the virus spreads. The current study considers the characteristics and issues related to universities moving towards online and blended learning during this period of universal isolation. Through focus group interviews conducted in South Korea and Malaysia, the study provides recommendation for the improvement of online classes and blended learning. The use of student focus groups gives the research an alternative perspective with which to assess the satisfaction level, success, and quality of online learning programs during the COVID-19 pandemic. Results from the focus groups show that for the success of online learning to become a reality, blended education should be considered to bolster learning. Further, results show that communication between lecturers and students remains a fundamental factor for success, regardless of the class category incorporated. Consequently, the results of the study provide further insight into matters experienced by students during the pandemic, and how educators may heed the opinions of students when improving future related blended learning programs.